THE IMPACT OF THE HUMAN FACTOR ON THE VEGETATION COVER OF THE EARTH'S ECOSYSTEM - Umarov Bakhtiyorzhan son of Bekzod; Shamshiddinova Mushtariy Pattojon daughter (Web of Journals Publishing, 2024)
The article describes the research of geobotanists about the transformation of plant cover, measures to increase the diversity of biota in places. Also, scientific information is provided about the negative effects of human factors, production enterprises and techniques on the flora and ways to reduce them.
Keywords: Biodiversity, transformation, dry desert, geobotanical research, plant cover, ecological balance, coniferous-wort.